Stages and the Relationship between Practices and Skills of Islamic Education Teachers in al-Qur'an and Fardhu Ain Classes (GPI-KAFA) - Muhammad Bin Abu Bakar; Mohd, Aderi Che Noh; Mohd. Waffi Albaraq bin Mokmin Basri (International Journal of Learning and Education, 2025)
Effective teaching and learning of the Quran and Fardhu Ain classes can be achieved through quality pedagogical practices. Islamic Education teachers for Quran and Fardhu Ain classes (GPI KAFA) play a vital role in improving the level of pedagogical teaching based on Islamic thinking. Increasing knowledge in pedagogical teaching can create a new line of pedagogy in KAFA Education. The purpose of this study is to identify the elements of teaching practices, teaching skills, communication skills, and teacher personality among GPI KAFA. This study is a quantitative study that obtained data through questionnaire data collection. The study involved 104 GPI KAFA teachers in the state of Selangor. Descriptive statistics, including mean, percentage, frequency, and standard deviation, were used to report the findings of this study. The findings show that the mean for all four constructs is at a high level; teaching practices (mean: 4.53, sd: 0.370), teaching skills (mean: 4.27, sd: 0.366), communication skills (mean: 4.69, sd: 0.463), and personality (mean: 4.69, sd: 0.366). The implications of this study are to increase pedagogical skills and social competence in teaching. This study has a positive impact on empowering GPI KAFA through continuous training and pedagogical skills.